Antioxidant and Antibacterial Activities of Chitosan Oligosaccharides Hydrolyzed Using Isolate T. harzianum KTR3 and A. sydowii KTR50 - Budiman Muhammad Arief; Tarman Kustiariyah; Hardiningtyas Safrina Dyah (BIO Web of Conferences)
Marine endophytic fungi Trichoderma harzianum KTR3 and Aspergillus sydowii KTR50 exhibit enzymatic activity capable of hydrolyzing chitosan into chitosan oligosaccharides (COS). This hydrolysis process reduces the molecular weight of chitosan, thereby enhancing its antioxidant and antibacterial activities. The study showed that COS with lower molecular weights demonstrated higher free radical scavenging activity against DPPH and ABTS•+ compared to untreated chitosan. However, antioxidant activity tests using Ferric Reducing Antioxidant Power (FRAP) and nitric oxide radical scavenging assays revealed no significant differences between COS and untreated chitosan. Additionally, COS hydrolyzed by fungal isolates exhibited better antibacterial activity against Escherichia coli (Gram-negative bacteria) and Staphylococcus aureus (Gram-positive bacteria) compared to untreated chitosan, although the antibacterial activity of all samples remained relatively weak. The antibacterial activity exhibited by both chitosan and COS was bactericidal. These findings indicate that COS hydrolyzed by T. harzianum KTR3 and A. sydowii KTR50 can reduce molecular weight, enhance certain antioxidant activities against tested radicals, and improve antibacterial activity.